Impact of Village Banking on Members' Livelihood: A Case Study of Serenje Central, Zambia - , Enock Phiri; , Hanson Chishimba (Archives of Current Research International, 2025)
This study analyzed the role of village banking on member’s livelihood in Serenje District, Zambia. The cornerstone of poverty reduction for individual, household, and community development is based on easy access to financial services. The concept of village banking can be traced back to ancient societies, where informal savings and credit groups provided a safety net for community members. It is a microcredit methodology whereby financial services are administered locally rather than centralized in a formal bank. To operationalize the study, a mixed research methodology was used. A sample size of 136 participants were drawn using Andrew Fish’s Formula from the 16 Village Bank groups. Questionnaires and Interview guide were used to collect both quantitative and qualitative data. This methodological blend not only facilitated exploration of the research objectives but also allowed for a robust analysis of the collected data. Data was analysed using IBM SPSS version 21.0 for quantitative data while thematic analysis was used for qualitative data. The study found that 27% of participants invest resources from village bank in businesses, while 31% of participants use the funds for everyday necessities. In terms of challenges, the study established that delays in fund share-out undermined the trust and confidence of participants in microfinance institutions, leading to dissatisfaction and potential attrition. To address the underlying challenges, the study recommends that participants must be trained and empowered to run and manage local finance groups using basic knowledge and tools and that these groups must be regulated to help protect members resources. The findings revealed challenges revolving around the extended waiting period to break the Village Bank circle. Participants find the waiting duration too lengthy for their investments, prompting some to seek loans from other, often more expensive, sources.